1512 Validity of the Clinical Neurological State in Diagnosing Diabetic Peripheral Neuropathy. (October 2012) - Hoeliner, I; Haslinger, V; Lütschg, J; Müller, G; Seick, D; Fussenegger, J; Zanier, U; Saely, C; Drexel, H; Simma, B
Abstract : Objective: We aimed to evaluate the prevalence of diabetic peripheral neuropathy (DPN) in children and adolescents with type 1 diabetes mellitus (T1DM) and examine whether the clinical neurological state validly diagnoses DPN as compared to the gold standard of nerve conduction velocity (NCV) in these patients. Methods: We measured NCV in an unselected consecutive series of patients aged 8–18 years who had been suffering from T1DM for at least one year. The clinical neurological state of these patients was examined using a protocol including ankle reflex, vibration, pin-prick, and temperature testing as well as a standardized questionnaire; neuropathy disability scores (NDS) and neuropathy symptom scores (NSS) were assessed. Results: Of our 39 patients, six (15%) had clinically evident DPN, whereas NCV testing revealed DPN in 15 (38%) patients. Sensitivity and specificity of the clinical neurological exam for the diagnosis of DPN as compared to the gold standard of pathological NCV were 40% and 100%, respectively. The corresponding positive and negative predictive values were 100% and 72.7%, respectively. Conclusion: In children and adolescents with T1DM DPN is highly prevalent, but in the majority of patients it is subclinical. Sensitivity and negative predictive values of the clinical neurological exam are low. Therefore, routine NCV measurement for the assessment of DPN appears warranted in these patients.